Effect of Seed Mycoflora in Producing Abnormal Seedling in Rice (Oryza sativa) Hybrids and its Parental Lines - HUYNH VAN NGHIEP; ASHOK GAUR; O.K. SHARMA (Seed Research, 2026)
Two rice hybrids and their parental lines were collected from Haryana and Andhra Pradesh of India in 2003. These seed lots were used to study the role of Bipolaris oryzae in producing abnormal seedlings. At the end of germination test, abnormal seedlings were separated and classified into different categories of abnormal seedlings according to their external morphology. These abnormal seedlings were transferred to the top of wet blotters in Petri dishes and incubated at 20°C under 12 h alternating cycles of NUV light and darkness. Generally, 3 to 4 days were optimal for the fungi to sporulate for recording the fungus associated with the different categories of abnormal seedlings.